Development of bufferless gel electrophoresis chip for easy preparation and rapid DNA separation. Issue 3 (17th October 2017) - Oleksandrov, Sergiy; Aman, Abdurazak; Lim, Wanyoung; Kim, Younghee; Bae, Nam Ho; Lee, Kyoung G.; Lee, Seok Jae; Park, Sungsu
Abstract: This work presents a handy, fast, and compact bufferless gel electrophoresis chip (BGEC), which consists of precast agarose gel confined in a disposable plastic body with electrodes. It does not require large volumes of buffer to fill reservoirs, or the process of immersing the gel in the buffer. It withstands voltages up to 28.4 V/cm, thereby allowing DNA separation within 10 min with a similar separation capability to the standard gel electrophoresis. The results suggest that our BGEC is highly suitable for in situ gel electrophoresis in forensic, epidemiological settings and crime scenes where standard gel electrophoresis equipment cannot be brought in while quick results are needed.